2007
DOI: 10.3171/jns.2007.106.6.1070
|View full text |Cite
|
Sign up to set email alerts
|

Use of 5-aminolevulinic acid in fluorescence-guided resection of meningioma with high risk of recurrence

Abstract: It has been established that fluorescence-guided resection using 5-aminolevulinic acid (5-ALA) is useful in glioma surgery. The authors report on a 65-year-old woman who had a huge atypical left-hemisphere meningioma, which extended into the skull and to the superior sagittal sinus and demonstrated fluorescence in response to administration of 5-ALA. After the tumor was removed, the operative field was observed under the fluorescent mode of a fluorescence surgical microscopy system. Several minute areas of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 20 publications
5
84
1
3
Order By: Relevance
“…Our observations, as well as publications of other authors [18,19], indicate that FN allows to obtain additional information about the infiltrative tumor growth and bone invasion. Therefore, this method may be very useful for surgery in Table 2 Linear correlation between the video fluorescence visually perception and spectroscopic fluorescence recurrence meningioma [19], skull base meningiomas [8], and spinal meningiomas [11].…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Our observations, as well as publications of other authors [18,19], indicate that FN allows to obtain additional information about the infiltrative tumor growth and bone invasion. Therefore, this method may be very useful for surgery in Table 2 Linear correlation between the video fluorescence visually perception and spectroscopic fluorescence recurrence meningioma [19], skull base meningiomas [8], and spinal meningiomas [11].…”
Section: Discussionmentioning
confidence: 56%
“…However, using 5-ALA in meningioma surgery has been studied only occasionally. Apart from the present research, which was also partly described in a previous publication [22], the most prominent series of meningioma operated on using FN were published by Collucia et al (33 patients) [18] and Kajimoto et al (27 patients) [19]. Both studies reported on convexity, parasagittal, and basal meningiomas of different malignancy degrees.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations